2014
DOI: 10.1002/jbt.21547
|View full text |Cite
|
Sign up to set email alerts
|

Tl+ Showed Negligible Interaction with Inner Membrane Sulfhydryl Groups of Rat Liver Mitochondria, but Formed Complexes with Matrix Proteins

Abstract: The effects of Tl(+) on protein sulfhydryl (SH) groups, swelling, and respiration of rat liver mitochondria (RLM) were studied in a medium containing TlNO3 and sucrose, or TlNO3 and KNO3 as well as glutamate plus malate, or succinate plus rotenone. Detected with Ellman's reagent, an increase in the content of the SH groups was found in the inner membrane fraction, and a simultaneous decline was found in the content of the matrix-soluble fraction for RLM, incubated and frozen in 25-75 mM TlNO3 . This increase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Some possible toxic mechanisms of Tl + can be the disturbance of calcium homeostasis, inhibition of cellular respiration, as well as ligand formation of Tl + with protein sulfhy dryl groups [1]. Our in vitro studies with RLM have revealed that Tl + was able to form complexes with mitochondrial proteins [35]. In our experiments, we observed that the inhibition of Ca 2+ influx with Ca 2+ free EGTA solution prevented the sustained/ transient increase in [Ca 2+ ] i induced by the addition of Tl + (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some possible toxic mechanisms of Tl + can be the disturbance of calcium homeostasis, inhibition of cellular respiration, as well as ligand formation of Tl + with protein sulfhy dryl groups [1]. Our in vitro studies with RLM have revealed that Tl + was able to form complexes with mitochondrial proteins [35]. In our experiments, we observed that the inhibition of Ca 2+ influx with Ca 2+ free EGTA solution prevented the sustained/ transient increase in [Ca 2+ ] i induced by the addition of Tl + (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the Tl + -induced MPTP opening can occur only in experiments with Ca 2+ -preloaded mitochondria. Unlike Tl + , bivalent heavy metal ions (Cd 2+ , Hg 2+ , Pb 2+ , and Zn 2+ ) and Ag + possess high affinity to molecular SH groups and can stimulate the MPTP opening in media free of Ca 2+ ( [69] and references inside). Therefore, another reason that Tl + only stimulates the opening of MPTP pores in Ca 2+ -contained media could be weak interaction of Tl + with the SH groups [69].…”
Section: Discussionmentioning
confidence: 98%
“…Unlike Tl + , bivalent heavy metal ions (Cd 2+ , Hg 2+ , Pb 2+ , and Zn 2+ ) and Ag + possess high affinity to molecular SH groups and can stimulate the MPTP opening in media free of Ca 2+ ( [69] and references inside). Therefore, another reason that Tl + only stimulates the opening of MPTP pores in Ca 2+ -contained media could be weak interaction of Tl + with the SH groups [69]. It was shown that both the increase of cytoplasmic Ca 2+ concentration and various cytotoxic effects in experiments with isolated hepatocytes and Tl + were decreased in the presence of MPTP inhibitors (CsA and carnitine), which is in good correspondence with the inhibition of Tl + -induced MPTP opening in CaRLM in the presence of the MPTP inhibitors (CsA and ADP) [3].…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that Tl + ions exhibit strong cytotoxic activity and inhibit the cancer drug resistance-associated protein that acts as an efflux pump [4]. Incorporation of Tl + into a “non-leaking” nanosized container equipped with a targeted delivery system could allow one to develop an efficient tool for tumor destruction, while the overall toxicity of Tl + can be significantly mitigated.…”
Section: Introductionmentioning
confidence: 99%